Use of technologies in a classroom: a comparative analysis of two schools, a public and a private - Santana Bittencourt, Priscilla Aparecida [UNESP]; Albino, Joao Pedro [UNESP] (Centro Univ La Salle-rj, 2017)
The present work analyzed the data on the use of new technologies in the education of Bauru schools. With the evolution of technologies over the years young people have greater access to technologies and it's necessary for the teaching-learning process to adapt to this reality of the world today. Therefore this study presents a part of the results of research conducted in the postgraduate program in media and technology of FAAC Unesp of Bauru / SP. A comparative analysis was made of how technology is used within the classrooms of these schools in the city of Bauru / SP, a public school and another private school. The main objective of this work was to demonstrate comparative data on the use of technology in schools in Bauru / SP and to verify how digital technology is used in these two schools and in the teaching-learning process.
Keywords: Education; Teaching-learning; Technologies